Phase transition from a d(x(2)-y(2)) to d(x(2)-y(2))+id(xy) superconductor - Ghosh, Angsula [UNESP]; Adhikari, Sadhan K. [UNESP] (Elsevier B.V., 1998)
The temperature dependencies of specific heat and spin susceptibility of a coupled dx2-y2 + idxy superconductor in the presence of a weak dxy component are investigated in the tight-binding model (1) on square lattice and (2) on a lattice with orthorhombic distortion. As the temperature is lowered past the critical temperature Tc, first a less ordered dx2-y2 superconductor is created, which changes to a more ordered dx2-y2 + idxy superconductor at Tcl(< Tc). This manifests in two second order phase transitions identified by two jumps in specific heat at Tc and Tc1. The temperature dependencies of the superconducting observables exhibit a change from power-law to exponential behavior as temperature is lowered below Tc1 and confirm the new phase transition. © 1998 Published by Elsevier Science B.V. All rights reserved.
Keywords: dx2-y2 + idxy-wave superconductor; Specific heat; Susceptibility; Crystal lattices; Mathematical models; Phase transitions; Specific heat of solids; Superconducting transition temperature; Thermal effects; Coupled wave superconductors; Tight-binding model; High temperature superconductors